Trends in Vocational Education and Training Research : Proceedings of the European Conference on Educational Research (ECER), Vocational Education and Training Network (VETNET) - Nägele, Christof [Herausgeber]; Stalder, Barbara E. [Herausgeber] (My University, 2018)
"The papers included in the 2018 ECER proceedings from Bolzano are written by established and well-known researchers, by doctoral students and early career researchers. They tell stories about young people and adult learners in vocational education and training, about institutional actors, teachers, trainers and coaches, and about the political, economic and social conditions that shape school-based and workplace learning, and teaching and training in initial, higher and continuous VET. Altogether, the papers reflect the rich culture of VET and VET research in Europe and abroad. The proceedings align with other activities of VETNET within EERAs annual ECERs and beyond." (editors' abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); I 2.2 Europa; Berufsbildung; Berufsbildungspolitik; Berufsausbildung; Ausbildungsabbruch; Höhere Berufsbildung; Weiterbildung; Lehrerbildung; Europa